2015
DOI: 10.1016/j.jpeds.2015.01.039
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular Deficits following Youth Concussion

Abstract: Objective To characterize the prevalence and recovery of pediatric patients with concussion who manifest clinical vestibular deficits, and to describe the correlation of these deficits with neurocognitive function, based on computerized neurocognitive testing, in a sample of pediatric patients with concussion. Methods This was a retrospective cohort study of patients age 5–18 years old with concussion referred to a tertiary pediatric hospital-affiliated sports medicine clinic from 7/1/2010–12/31/2011. A rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
126
4
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 188 publications
(134 citation statements)
references
References 32 publications
3
126
4
1
Order By: Relevance
“…These figures are higher than most previous reports in youth rugby 15. Young athletes are more vulnerable to concussion and may be affected by more complicated recovery times and higher risk of adverse outcomes 11 12. In addition to the potential of acute catastrophic traumatic brain injury, there have been increasing concerns of potential long-term adverse effects of sports-related concussion particularly when multiple concussive blows are sustained over a lifetime 17–19.…”
Section: Concussionmentioning
confidence: 95%
See 1 more Smart Citation
“…These figures are higher than most previous reports in youth rugby 15. Young athletes are more vulnerable to concussion and may be affected by more complicated recovery times and higher risk of adverse outcomes 11 12. In addition to the potential of acute catastrophic traumatic brain injury, there have been increasing concerns of potential long-term adverse effects of sports-related concussion particularly when multiple concussive blows are sustained over a lifetime 17–19.…”
Section: Concussionmentioning
confidence: 95%
“…Concussion can have devastating outcomes if not identified or managed accordingly. This is particularly pertinent in adolescent and young athletes, as developing brains undergo a more complex and protracted recovery postconcussion in comparison to an adult 11 12…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Recently, studies evaluating the validity and prognostic value of vestibular and oculomotor examination have been completed. 5,6 These studies, however, focus on patients presenting to specialty sports medicine clinics, likely representing a specific cohort of injured patients, though have demonstrated that a portion of this specific population exhibits abnormalities on this testing. Over the past several years, guidelines and position statements have begun recommending the use of a routine a vestibular and oculomotor assessment for the concussed pediatric patient, 7 with the most recent International Consensus Statement on Concussion recommending vestibular and oculomotor testing by all providers evaluating concussion in the acute setting.…”
Section: Introductionmentioning
confidence: 99%
“…Dizziness is a common problem following mTBI 10. Post-traumatic dizziness as a symptom of acute mTBI has been noted to abate earlier than other symptoms such as fatigue and headache 20.…”
Section: Discussionmentioning
confidence: 99%
“…Up to 81% of these patients will have dizziness on initial examination,10 which has been shown to prolong recovery when compared with other initial symptoms 11. The aetiology of persistent post-traumatic dizziness may be peripheral or central in origin, affecting inner ear or central nervous system integration and output, respectively.…”
Section: Introductionmentioning
confidence: 99%